A CONVENIENT HIV SCREENING: ORAL RAPID TEST REVIEW OF LITERATURE - Devi Nasution; Tenny Setiani Dewi (ODONTO : Dental Journal, 2019)
Background: HIV testing is crucial in identifying and initiating the treatment of HIV/AIDS. In recent years, the Oral Rapid Tests (ORT) has become one of the most popular tests based on saliva. This paper aims to present the response from research subjects who took the ORT using OraQuick®.Discussion: A total of 2657 studies was obtained. Finally, 21 articles matched to our review. The 21 included studies showed the advantages of ORT such as comfortable 91%, easy to use 76%, quick results 54%, preferred choice 67%, maintains confidentiality 54% and other reasons. Our reviewed studies demonstrated the consistent high acceptability of the oral rapid test in HIV.Conclusion: The comforts stem from ORT with OraQuick® are being contributed by its easy to use characteristic and non-blood-withdrawn comfortable method